Education On The Use Of Qris As A Payment Tool To Increase The Productivity Of Msmes In Rural Communities - Safari, Apay; Riyanti, Anti; Alfiana, Alfiana; Astuti, Nelly; Ristati, Ristati (Universitas Pahlawan Tuanku Tambusai, 2024)
When conducting observations for 2 weeks in each of the villages of Cihanyir, West Java, Air Buluh village, Bangka Belitung, Lake Paris village, the stages of finding problems were MSMEs that were monotonous, less productive, less creative, and had a small market share. The author believes that the use of QRIS in these villages can solve the problems being experienced. The results in this article show 1. The author made observations for 3 days and found that the majority of MSMEs in these villages were less productive, less developed, and needed new innovations to overcome these problems. 2. The author/devotee believes that the use of QRIS can overcome these problems and discussed these innovations and proposals with MSME actors and MSME actors agreed. 3. The author/servant conducted education on the use of QRIS in theory and practice for 14 days and believes that the use of QRIS in rural MSMEs can increase productivity, creativity of MSMEs and expand market share (because knowing QRIS also makes you aware of other MSMEs).